Relatos de um viajante: investigações em torno do processo de construção da história de língua e de sujeito gaúcho - Delevati, Daiane da Silva (2014)
This paper aims to propose a reflection on the constitution of language and the gaúcho subject in history from the discourse of Auguste de Saint-Hilaire in Viagem ao Rio Grande do Sul (1887), taking into account the man in his history and considering the processes and pro- duction conditions of the reports. Thus, the research question that guides this work is: How is the discourse on language and on the gaúcho subject constituted in Viagem ao Rio Grande do Sul? In order to answer it, we employed the notions of language and subject from the discur- sive perspective, by investigating how the processes of paraphrase and polysemy are per- formed (cf ORLANDI, 2007a), to try to explain the movement of the senses present in the descriptions of the discourse on language and on gaúcho, besides observing how the discourse of civilization crosses the reports by Saint-Hilaire by superimposing the language of the civi- lized on the uncivilized. Therefore, we followed the theoretical assumptions of the French Discourse Analysis, founded by Michel Pêcheux, and the History of Linguistic Ideas, repre- sented by Sylvain Auroux, both developed in Brazil mainly by Eni Orlandi and José Horta Nunes, among others. The corpus of this work is the result of a selection that met the criteria for different situations throughout the report, but always taking into account the discourse on language and subject. After the analysis, we found that the reports hold a discourse of the traveler who lives in constant tension with language, which we design as parted language (cf MEDEIROS; PETRI, 2013a). If there is a heterogeneous language, there is also a heterogene- ous subject, who is sometimes civilized, sometimes is uncivilized. And thus they mean heter- ogeneous language and subject just as language, subject and senses find constantly moving.